Optimalisasi Sifat Mekanik Biokomposit PLA dengan Serat Arenga Pinnata - Imam Prabowo; Mochamad Chalid (Journal of Science, Technology, and Visual Culture, 2021)
Polymer composite materials have been widely used in various industries, including construction and automobile industries. However, they have caused one critical problem, namely pollution. Thus, to minimize the impact, the scientists and expertise develop a biodegradable material so that it will decompose in the nature and avoid the pollutions. One of the alternatives is polylactide acid polymer and arenga pinnata fiber. This research was focused on the addition of 10% up to 30% amount of fiber to increase the mechanical properties of polymer composite with polylactide acid as a matrix and arenga pinnata fiber as a reinforcement agent. The mechanical properties were obtained by using universal testing machine and FESEM to observe the morphological structure. The results show that the mechanical properties especially tensile strength and young modulus have increased after the addition of 10% up to 20%, for example, tensile strength has grown from 50.5 MPa to 66 MPa, while young modulus has gone up approximately 183.2 MPa to 330.4 MPa. The decline of mechanical properties when the 30% of fiber was added are due to the void formed by the volatile substances during the preparations.